The Effect of Mhd on Unsteady Flow of A Second Grade Fluid Film Over an Unsteady Stret Ching Sheet - Qasim, Hanan; Abdulhadi, Ahmed (Iraqi Journal of Science, 2024)
The aim of this paper is the study of the influence of magnetic field on unsteadyflow of the second-grade fluid with constant viscosity. The equations whichcontrolled this type of fluid flow are complicated, so finding an analytical solution isnot easy, because it is a system of partial differential equations.We obtained anexpression for the velocity by using homotopy analysis method HAM.It is found that the equations motion are controlled by many dimensionlessparameter, namely magnetic field parameter M and material constant α,dimensionless film thickness β and unsteadiness parameter S.We have been studiedthe influence of all the physical parameters, that mentioned above on the velocityfield, also a comparison study among unsteady flow and unsteady flow under theinfluence of the magnetic field had been done.This study is done through drawingabout 75 graph by using the Mathematica package.